2006
DOI: 10.1071/py06044
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Level of Comfort with an Advanced Practice Role for Registered Nurses in General Practice: A Queensland, Australia, Study

Abstract: with nurses performing what may be considered traditional roles of the practice nurse. They were less comfortable with the more extended roles that are seen more as the traditional role of the general practitioner. However for no procedure were consumers uncomfortable in nurses performing that task. There were no differences in responses due to consumers' age, sex or previous contact with practice nurses.These results may be used to expand the role of practice nurses to complement the services provided by gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Despite the growing attention paid to satisfaction with general practice, internationally, limited research has been undertaken to explore consumer perceptions of general practice nursing [9-12]. Whilst some general practice satisfaction scales include a small number of items about nursing services, few collect sufficient information to provide a detailed insight into consumer perceptions of general practice nurses [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing attention paid to satisfaction with general practice, internationally, limited research has been undertaken to explore consumer perceptions of general practice nursing [9-12]. Whilst some general practice satisfaction scales include a small number of items about nursing services, few collect sufficient information to provide a detailed insight into consumer perceptions of general practice nurses [12].…”
Section: Introductionmentioning
confidence: 99%
“…Research has found a widespread acceptance of PNs in Australia and consumer support for a potentially more autonomous role in chronic disease management (Cheek et al. 2002, Hegney et al. 2006, Halcomb et al.…”
Section: Introductionmentioning
confidence: 99%
“…This is being facilitated by recent government initiatives (Australian Government Department of Health and Ageing 2011). Research has found a widespread acceptance of PNs in Australia and consumer support for a potentially more autonomous role in chronic disease management (Cheek et al 2002, Hegney et al 2006, Halcomb et al 2011. However, patient satisfaction with this role has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Their questionnaire, completed by 1343 general practice patients in Scotland, revealed that if patients were informed of nurses' capabilities they would be accepting of nurses taking on roles previously undertaken by general practitioners. A similar study [11] in Australia also found that patients (n=106) were comfortable with nurses in general practice expanding their roles. However in a qualitative study that interviewed 28 patients in the United Kingdom, Redsell et al, [12] found that patients continued to prefer general practitioners to nurses due to their perceived greater skills, knowledge and authority.…”
Section: Literature Reviewmentioning
confidence: 83%